Chronic Health Conditions and Children in Foster Care: Determining Demographic and Placement-Related Correlates. Issue 4 (20th October 2017) - Dunnigan, Allison E.; Thompson, Tess; Jonson-Reid, Melissa; Drake, F. Brett
ABSTRACT: Youth in foster care are more likely to experience health problems such as asthma compared to youth who are not in foster care. Data from a longitudinal study of youth in out-of-home care in one Midwestern metropolitan area were used to examine the association between placement-related factors and receiving treatment for asthma. Controlling for sociodemographic characteristics, youth who experienced more than one asthma spell, who were African American, or who had an internalizing mental health diagnosis were at increased risk of asthma. The finding that placement-related factors are associated with asthma in foster care youth raises implications for health service delivery.